1999
DOI: 10.1126/science.284.5412.321
|View full text |Cite
|
Sign up to set email alerts
|

Severe Liver Degeneration in Mice Lacking the IκB Kinase 2 Gene

Abstract: Phosphorylation of inhibitor of kappa B (IkappaB) proteins is an important step in the activation of the transcription nuclear factor kappa B (NF-kappaB) and requires two IkappaB kinases, IKK1 (IKKalpha) and IKK2 (IKKbeta). Mice that are devoid of the IKK2 gene had extensive liver damage from apoptosis and died as embryos, but these mice could be rescued by the inactivation of the gene encoding tumor necrosis factor receptor 1. Mouse embryonic fibroblast cells that were isolated from IKK2-/- embryos showed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
650
5
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 920 publications
(703 citation statements)
references
References 23 publications
42
650
5
4
Order By: Relevance
“…These studies did not examine endogenous NF-B-dependent promoters, nor did they look at cytokine gene expression induced by LPS (59,60). Moreover, IKK1dn could be equally effective as IKK2dn (60), a result that is inconsistent with evidence from mice deficient in these molecules (21,22,(25)(26)(27). In addition, our findings suggest significant differences in LPS signaling between macrophages and endothelial cells or fibroblasts.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…These studies did not examine endogenous NF-B-dependent promoters, nor did they look at cytokine gene expression induced by LPS (59,60). Moreover, IKK1dn could be equally effective as IKK2dn (60), a result that is inconsistent with evidence from mice deficient in these molecules (21,22,(25)(26)(27). In addition, our findings suggest significant differences in LPS signaling between macrophages and endothelial cells or fibroblasts.…”
Section: Discussioncontrasting
confidence: 59%
“…Much more likely and more therapeutically attractive would be the selective inhibition of upstream molecules such as I B kinase 2 (IKK-2), a kinase previously shown to be essential for TNF␣-and IL-1-induced I B␣ degradation, NF-B activation, and cytokine expression (21)(22)(23)(24)(25)(26)(27)(28). One study recently demonstrated that IKK-2 is an important kinase required for TNF␣-or IL-1-induced NF-B activation and expression of IL-6, IL-8, intercellular adhesion molecule 1, and MMP-1 in passaged synoviocytes (29), although the significance of these observations in terms of the treatment of RA is not clear.…”
mentioning
confidence: 99%
“…The phenotype of GSK-3b-deficient mice (Hoeflich et al, 2000) is strikingly similar to the phenotype displayed by IKK-b-or RelA-deficient mice and characterized by embryonic death caused by increased apoptosis in the liver (Beg et al, 1995;Li et al, 1999). Moreover, mouse embryonic fibroblasts derived from these animals are more sensitive towards tumour necrosis factor-a-induced apoptosis than wildtype fibroblasts because of the inability of these mouse embryonic fibroblasts to induce NF-kB (Hoeflich et al, 2000).…”
mentioning
confidence: 81%
“…The liver degeneration phenotype observed in FIP200 KO embryos is similar to the KO embryo phenotypes by deletion of several components in TNFα survival signaling pathways including Rel A, IKK-β, IKK-γ, GSK-3, MKK4, MKK7, or c-Jun, which are characterized by mid/late gestational lethality associated with increased apoptosis in liver [41][42][43][44][45][46][47]. Furthermore, FIP200 KO MEFs exhibit increased apoptosis upon TNFα treatment, which might be explained by the loss of FIP200 interaction with ASK1 and TRAF2, regulation of TRAF2-ASK1 interaction and ASK1 phosphorylation [12].…”
Section: The Role Of Fip200 In Embryonic Developmentmentioning
confidence: 60%